2015
DOI: 10.1016/j.diff.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The cellular and molecular progression of mitochondrial dysfunction induced by 2,4-dinitrophenol in developing zebrafish embryos

Abstract: The etiology of mitochondrial disease is poorly understood. Furthermore, treatment options are limited, and diagnostic methods often lack the sensitivity to detect disease in its early stages. Disrupted oxidative phosphorylation (OXPHOS) that inhibits ATP production is a common phenotype of mitochondrial disorders that can be induced in zebrafish by exposure to 2,4-dinitrophenol (DNP), a FDA-banned weight-loss agent and EPA-regulated environmental toxicant, traditionally used in research labs as an uncoupler o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 117 publications
(136 reference statements)
4
30
0
Order By: Relevance
“…As in a previous study, two embryos per well were necessary at the 7–30 hpf stages and three embryos per well were required at the 3 hpf stages, in order to achieve sufficient OCR levels. With 3‐h exposure to 0.5 μM DNP, beginning at 3hpf, basal OCR levels were significantly increased in zebrafish embryos (Bestman et al , ). In comparison, we found that basal respiration of 24 hpf embryos is also increased due to TCS exposure for 1 h at 15 and 30 μM (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in a previous study, two embryos per well were necessary at the 7–30 hpf stages and three embryos per well were required at the 3 hpf stages, in order to achieve sufficient OCR levels. With 3‐h exposure to 0.5 μM DNP, beginning at 3hpf, basal OCR levels were significantly increased in zebrafish embryos (Bestman et al , ). In comparison, we found that basal respiration of 24 hpf embryos is also increased due to TCS exposure for 1 h at 15 and 30 μM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They also validated the XF e 24 measurements with the Clark electrode method (Stackley et al , ). Another XF‐24 study analyzed the bioenergetics effects of the known mitochondrial uncoupler 2,4‐dinitrophenol (DNP) on 3–72 hpf zebrafish (Bestman et al , ). However, these published studies have utilized relatively low‐throughput 24‐well plates, time‐consuming placement of islet capture screens and multiple fish per well (required to attain suitable signal‐to‐noise ratios).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, even apparently adaptive responses may not preclude longer-term toxicity. For example, acute exposure of developing Danio rerio to the mitochondrial uncoupler 2,4-dinitrophenol resulted in an increase in gene expression of opa1 and peo1 (mtDNA helicase and twinkle homolog, required for mtDNA replication) immediately following the exposure, as the mitochondria fused and replicated as an initial stress response (Bestman et al 2015). However, at increasing time intervals following the initial exposure, opa1, peo1, and drp1 expression decreased, followed by a decrease in overall mitochondrial respiratory capacity, as well as motor neuron and retinal developmental defects.…”
Section: Mitochondrial Fusion and Fission As Stress Responsesmentioning
confidence: 99%
“…In recent years, the deleterious effect of environmental toxins on mitochondrial function has been studied extensively in humans (Eldakroory et al, 2016, Cremonese et al, 2017, Hongsibsong et al, 2017, Sittitoon et al, 2017) and model organisms such as rodents (O’Brien and Wallace, 2004, Suzuki et al, 2008, Butenhoff et al, 2009, Butenhoff et al, 2012), fish (Ge et al, 2017), zebrafish (Bestman et al, 2015, Liu et al, 2015, Jia et al, 2016, Chen et al, 2016, Raftery et al, 2017), Caenorhabditis elegans ( C. elegans ) (Zhou et al, 2013, Liu et al, 2015, Wyatt et al, 2017), and cellular models (Zieminska et al, 2016, D’Mello et al, 2017, Yang et al, 2017). A large number of environmental factors including l-methyl-4phenyl-l, 2, 3, 6-tetra-hydropyridine (MPTP), and pesticides such as rotenone and paraquat are now widely-recognized mitochondrial toxins (Backer and Weinstein, 1980, Harmon and Sanborn, 1982, Nicklas et al, 1987, Youngster et al, 1987) and specifically, neurotoxins.…”
Section: Environmental Toxins and Deleterious Effect On Mitochondriamentioning
confidence: 99%